2015
DOI: 10.1002/pssb.201451747
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of strained Mn5Ge3nanoislands on Ge(001)

Abstract: We report on the epitaxial growth of Mn5Ge3 on Ge(001) by molecular beam epitaxy using solid phase epitaxy method. Mn5Ge3 grows as nanoislands, which are randomly distributed over the substrate surface. Select area electron diffraction analysis was used to determine the epitaxial relationship Mn5Ge3(001)[110]//Ge(001)[110], as well as to detect an induced tensile strain along [110] Mn5Ge3 direction to fit the Ge lattice, while the observation of Moiré patterns indicates a complete relaxation along the [11¯0] d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…A subsequent anneal of the nanoislands leads to the formation of Mn 5 Ge 3 as demonstrated by Olive et al The growth of the Mn 5 Ge 3 phase on Ge(001) is remarkable because it is endotaxial: its interface is buried in the substrate, as shown in Figure d. Indeed, only part of the island emerges from the surface, the rest being buried in the substrate of Ge(001).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…A subsequent anneal of the nanoislands leads to the formation of Mn 5 Ge 3 as demonstrated by Olive et al The growth of the Mn 5 Ge 3 phase on Ge(001) is remarkable because it is endotaxial: its interface is buried in the substrate, as shown in Figure d. Indeed, only part of the island emerges from the surface, the rest being buried in the substrate of Ge(001).…”
Section: Resultsmentioning
confidence: 80%
“…35 The similarities in spatial distribution, shape and density between the nanoislands (Fig. 5a) and the nanocolumns system A subsequent anneal of the nanoislands leads to the formation of Mn 5 Ge 3 as demonstrated by Olive et al 37 The growth of the Mn 5 Ge 3 phase on Ge(001) is remarkable because endotaxial: its interface is buried in the substrate, as shown in Fig. 5d.…”
Section: Mn-induced Nanoislandsmentioning
confidence: 71%
See 1 more Smart Citation
“…It has been demonstrated that Mn 5 Ge 3 /Ge(111) thin films, where the c axis of Mn 5 Ge 3 is perpendicular to the film plane, have their easy magnetization axis on the basal Mn 5 Ge 3 (001) plane, for films with thickness <25 nm [21]. This is an opposite behavior to the one of bulk or nanostructured Mn 5 Ge 3 , where the c axis is also the easy magnetization axis [17,21]. It has been observed that the magnetic anisotropy is directly related to the thickness of Mn 5 Ge 3 /Ge(111) films.…”
Section: Introductionmentioning
confidence: 99%
“…Mn 5 Ge 3 grown on Ge(111) is also proposed as a potential prospect for SC/FM heterostructures for spin injection [16]. However, the growth of Mn 5 Ge 3 on Ge(001) substrates has been scarcely investigated [9,[17][18][19]. Mn 5 Ge 3 /Ge(001)heterostructures offer the possibility of integration into the Si(001) production technology, as Ge epitaxial layers can be grown on Si(001) substrates, through a (001) SiGe interlayer [20].…”
Section: Introductionmentioning
confidence: 99%